High satisfaction and improved quality of life with Rock Steady Boxing in Parkinson's disease: results of a large-scale survey. Issue 20 (25th September 2022) - Larson, Danielle; Yeh, Chen; Rafferty, Miriam; Bega, Danny
Abstract: Purpose: To compare demographics, self-reported symptom burden, Health-Related Quality of Life (HRQL), and Self-Efficacy for Exercise (SEE) between participants and non-participants of Rock Steady Boxing (RSB), a non-contact boxing program for individuals with Parkinson's disease (PD) that focuses on agility, balance, and speed training. Materials and methods: Adults with PD who had heard of RSB completed a 20 min, 61-question electronic survey including the Parkinson's Disease Questionnaire-39 (PDQ-39) and the Self-Efficacy for Exercise (SEE) scale. Differences between participants and never-participants were analyzed using chi-squared test, fisher's exact test and Wilcoxon test. Results: Of 2054 individuals enrolled in the survey, 1709 were eligible for analysis. 1333 were current participants, 166 previous-participants, and 210 never-participants. RSB participants were median age 69, 59% male, and 97% Caucasian. The majority of current participants reported that RSB improved their social life (70%), fatigue (63%), fear of falling (62%), depression (60%), and anxiety (59%). Compared to previous and never-participants, current participants had better median PDQ-39 scores (36 and 32 vs 25, p < 0.01) and SEE scores (43 and 48 vs 54, p < 0.01). Conclusions: This is the largest survey of RSB use in PD. RSB participants report improvement in non-motor impairments and have significantly better HRQL and ESE compared to never-participants. IMPLICATIONS FOR REHABILITATION: Parkinson's disease (PD) is a slowly progressive neurodegenerative condition that affects motor function and subsequently, quality of life. Exercise is increasingly recognized as an important treatment for motor and non-motor symptoms of PD. Rock Steady Boxing (RSB) is a specific non-contact boxing program for PD that is growing and increasing in popularity, though there is limited data on its effect on PD symptoms and quality of life.